Kunsthallen Klaedefabrik Brandts 2000. (Odense : Kunsthalle Brandts Klaedefabrik, 2000)
Christiansen, Ursula Reuter ; Lundbye, Vagn ; Olsen, John ; Abrahamsen, Lars ; Jaar, Alfredo ; Bovin, Karl ; Rorup, Kai EistrupViggo ; Krause, Ellen ; Philipsen, Theodor ; Christiansen, Poul S. ; Swane, Sigurd ; Arnoldi, Per ; Johansson, Peter ; Fabre, Jan ; Kim, Soo-Ja ; Yan Pei-Ming
Overzicht tentoonstellingen 2000
Engels
boek